On M. G. Krein's papers in the theory of spaces with an indefinite metric - Azizov, T. Ya.; Ginsburg, Yu. P.; Langer, H. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
This is a surv ey of the papers by M. G. Krein (and his disciples) devoted to the theory of operators in the spaces with indefinite metric and its applications.